2019
DOI: 10.1111/bjd.18684
|View full text |Cite
|
Sign up to set email alerts
|

Young people's perceptions of acne and acne treatments: secondary analysis of qualitative interview data

Abstract: Summary Background Acne vulgaris is a common skin condition affecting approximately 95% of adolescents to some extent. First‐line treatments are topical preparations but nonadherence is common. A substantial proportion of patients take long courses of oral antibiotics, associated with antibiotic resistance. Objectives This study aimed to explore young people's views and experiences of acne and its treatments. Methods We report a secondary thematic analysis of interview data collected by researchers in the Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…Participants described treatment as ‘keeping their acne at bay’, being only partially effective or not working at all. 14 19 This appeared to have implications for acne management, with disappointment leading to stopping treatment early or opting for alternative treatments in the absence of ‘instant’ results.…”
Section: Resultsmentioning
confidence: 99%
“…Participants described treatment as ‘keeping their acne at bay’, being only partially effective or not working at all. 14 19 This appeared to have implications for acne management, with disappointment leading to stopping treatment early or opting for alternative treatments in the absence of ‘instant’ results.…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative research into patients with acne has similarly found a perception of low effectiveness of topical treatments in comparison with oral antibiotics. 18 However, to the authors’ knowledge, the present study is the first to show that many GPs also hold this view and to explore the implications of GPs’ perceptions of patient expectations about antibiotic prescribing for acne. One previous qualitative study of GPs’ views of acne management found that GPs perceived patients’ non-adherence to topical treatments as a barrier to treatment success but that they rarely signposted patients to written information sources.…”
Section: Discussionmentioning
confidence: 82%
“…Semi-structured interviews were conducted by telephone between March 2018 and March 2019 by one author (DP). The interview guide was based on the available literature (2,18) and study aims and is shown in Box 1. The guide was developed and piloted prior to commencing interviews and minor revisions to wording made following the first two interviews.…”
Section: Interviewsmentioning
confidence: 99%
“…On the other hand, acne vulgaris is not only a highly treatable condition but also one that should be taken seriously and treated early. It has been shown that patients often delay treatments for up to 1 year after symptom occurrence, and that some may view acne as a short‐lived, self‐resolving condition not requiring treatment 4 . Furthermore, primary nonadherence for acne treatments is already high, with up to 27% of patients not initiating medications within 3 months of prescription 5 .…”
mentioning
confidence: 99%